Non-optimizing growth-cum-debt models and sustainability of indebtedness - Jesko Hentschel (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1988)
In the past few years, the role of international organizations involved in supplying developing countries with capital has changed - not only have they increased their volume of lending, but they have also become catalytic agents stimulating continuing private bank lending to less developed countries. The hesitation of the private banks 'to throw good money after bad money' apparently rests on the evaluation that quite a few developing countries will never be able to pay back the loans or even the interest on them. In order to persuade private banks to increase their loans, international organizations stress that the current debt crisis is one of illiquidity rather than insolvency - if rescheduling agreements are reached and fresh money is made available to the developing countries, they will eventually be able to service their debt without relying on new loans. Private banks, on the other hand, have begun to judge major debtors as following an explosive debt accumulation path and characterize them as being insolvent in the long run. Economic models can try to point out the crucial characteristics determining whether a country follows a stable, sustainable debt path and is therefore able to eventually pay back foreign debt or an unstable, unsustainable debt path. In this respect, they might explain why the vdebt-cycle hypothesis' (a country first borrows from abroad and later repays the debt with corresponding balance of payments deficits and surpluses; compare World Bank 1985, p.47) apparently does not apply to quite a few developing countries. This hypothesis rests on the neoclassical production and trade theories and predicts that capital flows to countries or regions where the return to it is high and later leaves these areas, when the built-up capital stock has reduced the marginal productivity of capital. A developing country with a low capital stock first incurs and later repays the debt. This paper surveys models which try to explain why a country might not be able to service and repay its debt as predicted by the debt-cycle hypothesis. Section II provides the reader with a classification of models dealing with indebtedness. Section III analyses different characteristics of non-optimizing models. Results are reviewed in Section IV and the applicability and critique of these models is discussed in Section V.
Keywords: 330; Internationale Staatsschulden; Theorie; Entwicklungsländer